The Effect Of Per Capita Income, Cigarette Prices, And The Percentage Of The Population Smoking On Cigarette Consumption In Lampung Province 2020 – 2023 - Rizky Apriansyah; I Wayan Suparta; Resha Moniyana Putri (International Journal of Economics, Business and Innovation Research, 2024)
One consumption behaviour that has a significant impact on the economy and health is cigarette consumption. Lampung occupies the top position of cigarette consumption in Indonesia with a very significant increase in consumption of 13.6% over the past 3 years. This research is a descriptive and quantitative research. This study uses 3 independent variables, namely income per capita, cigarette prices, and percentage of the population smoking, and the dependent variable used in this study is cigarette consumption. The scope of this study covers 15 districts/cities in Lampung Province using 4 years of data from 2020-2023. Based on the tests that have been carried out, it is known that the variables of income per capita and the percentage of the population smoking have a positive and significant influence on cigarette consumption in Lampung Province in 2020-2023.